Archaeology of Mind in the Hebrew Bible/Archäologie alttestamentlichen Denkens - Wagner, Andreas 1963-; Oorschot, Jürgen van 1957-; Allolio-Näcke, Lars 1975-; Walter de Gruyter GmbH & Co. KG (Berlin/Boston De Gruyter, 2023)
Research into the Hebrew Bible, Ancient Near East, Philosophy and History have long considered whether thought in the cultural area of the ancient Middle East differs from that in the western Mediterranean. The inclusion of neurobiology, psychology, brain research and evolutionary research will widen this horizon and allow new approaches. This volume provides in depth insides into this Archaeology of Mind in 22 contributions
English
German
Keywords: Middle Eastern history; Ancient History; Religion and beliefs; Indigenous religions, spiritual beliefs and mythologies of the Americas; Psychology; Konferenzschrift -- 2018